2006
DOI: 10.1200/jco.2005.05.1896
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hormone Replacement Therapy on Menopausal Symptoms in Younger High-Risk Women After Prophylactic Salpingo-Oophorectomy

Abstract: A B S T R A C T PurposePreventive health strategies for women at increased hereditary risk of ovarian cancer include gynecologic screening (GS) and/or prophylactic oophorectomy (PBSO). Hormone replacement therapy (HRT) is often prescribed to compensate for postsurgical endocrine deficiencies. This study examined the impact of HRT use on levels of endocrine symptoms and sexual functioning among premenopausal women who have undergone PBSO. Comparisons were made with similar women undergoing GS. Patients and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
160
3
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(179 citation statements)
references
References 33 publications
(9 reference statements)
10
160
3
6
Order By: Relevance
“…111 Hormone-replacement therapy has demonstrated the ability to mitigate the endocrine symptoms and symptoms of lower sexual functioning, but not to presurgical levels. 112,113 These findings, along with reports by 60% of BRCA1/BRCA2 carriers that they would have liked more information about the procedure's impact on their sex lives before their RRSO, 114 highlight the potential benefit of referrals to sexual health clinics before surgery.…”
Section: Implications Of Cancer Genetic Testing/hirschberg Et Almentioning
confidence: 97%
“…111 Hormone-replacement therapy has demonstrated the ability to mitigate the endocrine symptoms and symptoms of lower sexual functioning, but not to presurgical levels. 112,113 These findings, along with reports by 60% of BRCA1/BRCA2 carriers that they would have liked more information about the procedure's impact on their sex lives before their RRSO, 114 highlight the potential benefit of referrals to sexual health clinics before surgery.…”
Section: Implications Of Cancer Genetic Testing/hirschberg Et Almentioning
confidence: 97%
“…These symptoms are worse when Hormone Replacement Therapy (HRT) is not used [17]. However, a study that compared at-risk women who underwent RRSO (n=29) to a control group of women who were also at-risk but opted for screening (n=28) found no difference between the groups in sexual functioning, although there was a trend for more menopausal symptoms (p=.06) in the surgery group [18].…”
Section: Introductionmentioning
confidence: 99%
“…20 In a Dutch study evaluating quality of life in high-risk women, no differences were observed in generic quality of life when comparing women who underwent PBSO with those undergoing gynecologic screening or women in the general population. 52 Although the group undergoing PBSO experienced worse sexual functioning and endocrine symptoms than women undergoing gynecologic screening 52 and these effects were not completely ameliorated by HRT, 53 the reduction in cancer worries and more favorable cancer risk perception effectively balanced out these effects in the PBSO study group. Therefore, we felt it was reasonable not to make QALY adjustments for women having prophylactic surgery.…”
Section: Quality Of Life Adjustmentmentioning
confidence: 99%